ANALISIS SENSORI PRODUK SOSIS SAPI KOMERSIAL MENGGUNAKAN PRINCIPLE COMPONENT ANALYSIS - Ni Wayan Putu Meikapasa; Lalu Danu Prima Arzani (The Journal of Teknologi Pangan, 2022)
The sensory characteristics of a product are one of the factors that determine the level of consumer acceptance. This study aimed to provide an overview of the differences in the sensory characteristics of commercial beef sausages. The study used three different brands of beef sausages (SG, SV, and SV) from different producers. The sensory attribute testing was carried out by 75 panelists. The sensory attributes tested were texture, color, aroma, mouthfeel, and meatiness of the product. Data were analyzed using one-way analysis of variance (ANOVA) with a confidence level of 95% (?=0.05) and followed by the Duncan test. Furthermore, to determine the variables that determine the sensory attributes of the product, multivariate analysis with principal component analysis (PCA) was used. The results of the study showed that the "SV" brand of beef sausage had a strong correlation with the sensory attribute of mouthfeel, and the "SB" brand of beef sausage had a strong correlation with the sensory attributes of meatiness and aroma and had a close correlation with the sensory attribute of texture. The "SG" brand of sausage had a strong correlation with the sensory attribute of color but had a negative correlation with the sensory attribute of texture.Keyword: beef sausage, PCA, Sensory